Business Continuity Planning for Government Cash and Debt Management - Balibek, Emre.; Storkey, Ian.; Yavuz, Hakan (Washington, D.C. : International Monetary Fund, 2021)
Cash and debt management operations are part of the 'transactional' functions of public financial management. It is critical that these functions are resilient to external disruptions, ranging from information and communication technology (ICT) system outages to natural disasters. This technical manual aims to provide guidance on the steps that government cash and debt management units can follow to develop and implement a practical business continuity plan that economizes the resources used. It also discusses the evolving nature of business disruption risks faced by cash and debt management over the last decade, including the COVID-19 pandemic, as well as risk mitigation solutions that have emerged.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: National Government Expenditures and Related Policies; Tax Evasion and Avoidance